2012
DOI: 10.1210/jc.2011-2284
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Hypopituitarism Is Rare after Structural Traumatic Brain Injury in Early Childhood

Abstract: Permanent hypopituitarism is rare after both inflicted and accidental structural TBI in early childhood. Precocious puberty was the only pituitary hormone abnormality found, but the prevalence did not exceed that of the normal population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 34 publications
6
46
4
Order By: Relevance
“…Heather and colleagues described a large number of 64 pediatric patients with inflicted injuries as part of a cross-sectional series of 198 patients and found no cases of permanent hypopituitarism at least 1 year after injury. 3 However, our study is different from the previous work in several important ways. Of course, we report far fewer patients than they did.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Heather and colleagues described a large number of 64 pediatric patients with inflicted injuries as part of a cross-sectional series of 198 patients and found no cases of permanent hypopituitarism at least 1 year after injury. 3 However, our study is different from the previous work in several important ways. Of course, we report far fewer patients than they did.…”
Section: Discussioncontrasting
confidence: 66%
“…However, prevalence of endocrine dysfunction after iTBI has been described in only one previous study. 3 Many case reports have documented pituitary dysfunction after TBI in individual children. However, few studies have systematically evaluated the prevalence of endocrine dysfunction in children after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…A study of 23 patients in the transition period (ages 16 to 25 years) found that hypopituitarism was present in 34.6% at 3 months after TBI, and at 12 months, hypopituitarism was present in 30.3% (13). On the other hand, the prevalence of hypopituitarism was only 8% in a study of 87 children and adolescents who were evaluated at 12 months after severe TBI (14), whereas in another study of 198 children with remote history of TBI in early childhood, low peak stimulated GH and cortisol levels were found in only 8% of the subjects (15).…”
Section: Epidemiologymentioning
confidence: 93%
“…However, recent data from large cohorts raised doubt about the evidence behind such recommendations, as they were unable to confirm the previously reported high prevalence of pituitary dysfunction (2,3,4). Although severe hypopituitarism may certainly present as a complication to brain injury, mostly mild and often irreproducible deficiencies have been reported.…”
Section: Introductionmentioning
confidence: 92%